Campanula oreodoxa (Campanulaceae), a new critically endangered species from the Aladagh Mountains, NE Iran - Arjmandi, Ali Asghar; Ejtehadi, Hamid; Memariani, Farshid; Joharchi, Mohammad Reza; Mesdaghi, Mansour (Phytotaxa, 2021)
Campanula oreodoxa (Campanulaceae) is described and illustrated as a new sub-alpine species from North Khorassan province, Iran. The new species belongs to C. sect. Oreocodon based on dehiscence of the capsules with three middle pores at the base and absence of appendages between the calyx lobes. It is compared morphologically with the closely related species including C. hystricula and C. lourica. The micromorphological characters of seed coat and pollen grains of the new species are presented and compared with the chasmophytic allies in the area. Notes on distribution, habitat characterization, and the associated flora are provided. The new species is assessed as critically endangered (CR) and the conservation value of the habitats in the area is discussed.